2021
DOI: 10.1158/1055-9965.epi-21-0443
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Risk in Relation to Blood Cholesterol and Triglycerides

Abstract: Background: The association between circulating cholesterol and triglyceride levels and ovarian cancer risk remains unclear.Methods: We prospectively evaluated the association between cholesterol [total, low-density lipoprotein (LDL-C), and highdensity lipoprotein (HDL-C)] and triglycerides and ovarian cancer incidence in a case-control study nested in the Nurses' Health Study (NHS) and NHSII cohorts and a longitudinal analysis in the UK Biobank.Results: A total of 290 epithelial ovarian cancer cases in the NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Intriguingly, our study found that among all biomarkers of AL score, higher levels of triglycerides and CRP were associated with 1.68 and 1.42 folds increased risk of cancer (triglycerides: HR = 1.68, 95% CI: 1.16, 2.43; CRP: HR = 1.42, 95% CI: 1.01, 2.01). The relationship between circulating glyceride and cancer risk has been reported previously [29,30]. In the metabolic syndrome and cancer project, Borena et al, reported that the relative risk of top quintile versus bottom quintile of triglycerides of overall cancer was 1.16 (95% CI: 1.06-1.26) in men and 1.15 (95% CI: 1.05-1.27) in women [29].…”
Section: Discussionmentioning
confidence: 69%
“…Intriguingly, our study found that among all biomarkers of AL score, higher levels of triglycerides and CRP were associated with 1.68 and 1.42 folds increased risk of cancer (triglycerides: HR = 1.68, 95% CI: 1.16, 2.43; CRP: HR = 1.42, 95% CI: 1.01, 2.01). The relationship between circulating glyceride and cancer risk has been reported previously [29,30]. In the metabolic syndrome and cancer project, Borena et al, reported that the relative risk of top quintile versus bottom quintile of triglycerides of overall cancer was 1.16 (95% CI: 1.06-1.26) in men and 1.15 (95% CI: 1.05-1.27) in women [29].…”
Section: Discussionmentioning
confidence: 69%
“…For example, Zhang et al [10] found a significant association between elevated TG levels and high severity of EOC. Another study found that blood TG levels at clinically relevant cut-off points (>200 vs. ≤200 mg/dL) for cases diagnosed for more than 2 years showed a positive relationship with EOC risk [26]. An increased concentration of TG was also observed in a Japanese EOC study [27].…”
Section: Discussionmentioning
confidence: 90%
“…In men, higher free testosterone, but not total testosterone, has been found to be associated with risk of prostate cancer [ 41 ]. Conversely, biomarkers of inflammation do not appear to be related to risk of glioma [ 70 ] and circulating lipid levels are not strongly associated with ovarian cancer risk [ 71 ]. Biomarkers can also be used to investigate the pathways between known risk factors and cancer diagnosis, with research showing that the increased risk of colorectal cancer associated with obesity is unlikely to be driven by adiposity-induced chronic inflammation, insulin resistance or sex-steroid hormone levels [ 72 ].…”
Section: Uk Biobank and Cancer Researchmentioning
confidence: 99%